2006
DOI: 10.1159/000091628
|View full text |Cite
|
Sign up to set email alerts
|

Distal Hypospadias Repair in Adults: The Results of 97 Cases

Abstract: Introduction: We reviewed our 9-year experience on 97 men with distal hypospadias who had undergone hypospadias surgeries. Subjects and Methods: Patients were divided into two groups: group 1 included 17 men who had one or more unsuccessful surgeries in their childhood, and group 2 included 80 men with no previous hypospadias repairs. Meatal positions were glanular in 6, coronal in 35 and subcoronal in 56 patients. Our 97 hypospadias surgeries involved 42 meatal advancement and glanuloplasty, 41 Mathieu and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…In this highly selected population, the overall success rate in our series seems higher than or similar to most series reported in literature. [5,[7][8][9][10] Senkul et al reported an overall success rate of 89.6% in 88 adult hypospadias patients with various techniques which is similar to ours. [6] Their postoperative complication rate was higher compared to children, and these patients more often required multiple interventions.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this highly selected population, the overall success rate in our series seems higher than or similar to most series reported in literature. [5,[7][8][9][10] Senkul et al reported an overall success rate of 89.6% in 88 adult hypospadias patients with various techniques which is similar to ours. [6] Their postoperative complication rate was higher compared to children, and these patients more often required multiple interventions.…”
Section: Discussionsupporting
confidence: 85%
“…Previous circumcision history is not mentioned in majority. [5][6][7][8][9][10][11]. In our prospective study, all patients underwent primary repair with TIPU by a single surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adayener and Akyol described 12 men who underwent TIP in a cohort of 80 with a mean age of 22 years with distal hypospadias. 6 The other patients were repaired by meatal advancement and glanuloplasty or the Mathieu technique. In 1 of the 12 men (8%) a fistula developed during followup at a mean of 19 months for a complication rate that was the same as the overall complication rate of 9%.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with hypospadias repair in adults is generally limited in developed countries [7]. However, hypospadias repair is frequently performed during adulthood in developing countries as a result of difficult economic and social conditions [8,9]. Because of the presence of the foreskin and proximity to the meatus to the glans, parents might not consider this situation as a problem.…”
Section: Discussionmentioning
confidence: 99%